2014
DOI: 10.5812/ircmj.6812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hearing Loss by OAE in Asphyxiated Newborns

Abstract: Background:Severe birth asphyxia (apgar < 7 at the 5th minute of birth) is recognized as a hearing loss risk factor by the joint committee on infant hearing (JCIH). About half of the newborns with hearing loss do not indicate any sign and risk factor at birth. Accordingly, the joint committee recommended performance of hearing screening test in 2000, especially for babies born with risk factors.Objectives:The aim of this study was to evaluate hearing loss in asphyxiated neonates. Early diagnosis would result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
13
1
3
Order By: Relevance
“…Also, in a study by Amini, a significant relationship was found between the mean birth weight and hearing loss; however, no statistical correlation was found between Apgar score and abnormal OAE [19] but, In the present study Apgar <5 and low weight birth were high-risk factors for hearing loss.…”
Section: Discussioncontrasting
confidence: 78%
“…Also, in a study by Amini, a significant relationship was found between the mean birth weight and hearing loss; however, no statistical correlation was found between Apgar score and abnormal OAE [19] but, In the present study Apgar <5 and low weight birth were high-risk factors for hearing loss.…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, in a study by Taghdiri, poor AABR results were significantly associated with hyperbilirubinemia and birth weight less than 1500 g ( 28 ). Also, in a study by Amini, no statistical correlation was found between 5-minute Apgar score and abnormal OAE; however, a significant relationship was found between the mean birth weight and abnormal OAE ( 30 ).…”
Section: Discussionmentioning
confidence: 90%
“…Long NICU stay duration is usually relevant to deteriorated health of infants, prematurity, mechanical ventilation and ototoxic antibiotic use [31]. Use of ventilators for more than 7 days was significantly related to failed TEOAE screening test (p<0.001), in consistence with results of Amini et al in Iran [32]. Continuous nasal positive airway pressure applied as a respiratory support for preterm neonates proved to be a risk factor for prolonged exposure to high levels of noise [33].…”
Section: Discussionmentioning
confidence: 84%